Novel drug-eluting stent to reduce fibrosis-induced ureteral stricture - Fong, Timothy Ren Zhong (2015)
Ureteral stents are often used by urologists in treating patients with urinary tract obstruction. Ureteral stricture in particular, can be attributed to the build-up of fibrosis during the scarring process. Studies have shown that Mitomycin C (MMC) impedes fibroblast proliferation and is effective in preventing fibrosis accumulation during scar formation. The application of low doses of MMC (2 mg/L and 10 mg/L) has been successful in reducing fibrosis for urethral stricture. The aim of this project is to synthesize a drug loaded coating with smooth morphology and identify the effect of thickness, drug loading and pH on the sustained release of MMC. A solution of poly(L-lactide-co-caprolactone) and MMC was spray coated on 2cm long polyurethane stents, with varied drug loading (2.5wt%, 5wt%, 7.5wt%). The stents were then immersed in four different Phosphate Buffer Saline mediums (pH 6, 7, 7.4, 8.5) for drug release over 28 days. High performance liquid chromatography and scanning electron microscopy were used to monitor the amount of drug released at various time points (10min, 30min, 6hr, 1,3,7,14,21 and 28 days) and to observe surface morphology of the coated stents respectively. From the release profiles for the four thickness values chosen (20μm, 46μm, 120μm, 240μm), it was observed that a thicker coating had a lower cumulative percentage release. The thickness of 46μm was used for subsequent pH and drug loading studies, as it was able to achieve the same daily amount of drug release as the higher thickness values, with less drug coated on the stent. It was also observed that a higher drug loading resulted in a lower cumulative percentage release. These observations are in agreement with the release theory of simple monolithic dispersions. In addition, the percentage of cumulative release in pH 6 was much lower than in pH 7, 7.4 and 8.5, which can be attributed to poor MMC stability in acidic medium. In conclusion, all the release study samples fabricated had smooth surface morphology and were observed to have sustained MMC release with no initial burst for the 28 day period. The results obtained will provide a reference standard for similar studies in the future.